2015
DOI: 10.1007/s13273-015-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin exerts preferential cytotoxic effects on malignant mesothelioma cells by inducing p53 expression, caspase-3 activation, and apoptosis

Abstract: Quercetin, a naturally occurring flavonoid, has been heralded as a promising chemopreventive agent. This study was undertaken to probe the mole cular mechanisms underlying the anticancer activity of quercetin in malignant mesothelioma (MM) cells. Quercetin at low doses elicited apoptotic cell death on MM MSTO211H cells, as signified by pyknotic and fragmented nuclei, increased annexin V binding, and increased proportion of cells with hypodiploid DNA. Preceding these changes, quercetin induced upregula tion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The membranes were then washed in TBST and incubated with the appropriate secondary antibody HRP-conjugated (1:5000) at room temperature for 1 h. The separated proteins were visualized using the ECL plus Western blotting detection system. The intensity of the bands was analyzed using ImageQuant TL software (GE Healthcare Bio-Science Corp., Piscataway, NJ) [26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…The membranes were then washed in TBST and incubated with the appropriate secondary antibody HRP-conjugated (1:5000) at room temperature for 1 h. The separated proteins were visualized using the ECL plus Western blotting detection system. The intensity of the bands was analyzed using ImageQuant TL software (GE Healthcare Bio-Science Corp., Piscataway, NJ) [26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours incubation at 37°C, the cells were treated with docetaxel solutions. Cellular viability was assessed by CCK-8 (Dojindo, Kumamoto, Japan) [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the study, the up-regulation of p53 induced by quercetin can be visualized at both mRNA and protein levels without altering its ubiquitination as well as enhancing caspase-3/7 activity and procaspase-3 and PARP cleavages. The subset of cells in the G2/M phase that has been obstructed by the pan-caspase inhibitor escalated later in a quercetin concentration-dependent approach [ 179 ]. Another study found that quercetin interacts with the human glioblastoma A172 as well as LBC3 cell lines, confirming increased ROS production, unregulated SOD1 and SOD2 expression, ATP depletion, and CHOP8 overexpression, and as a result, apoptosis of these brain cancer cell lines.…”
Section: Molecular Mechanism For Quercetin-induced Cancer and Cancer ...mentioning
confidence: 99%